2009
DOI: 10.1039/b819476a
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable access to fluoroalkylated trisubstituted alkenes via highly stereoselective cobalt-catalyzed hydrosilylation reaction of fluoroalkylated alkynes

Abstract: Hydrosilylation reaction of various fluoroalkylated alkynes with Et(3)SiH in the presence of a catalytic amount of Co(2)(CO)(8) was investigated. The hydrosilylation of the alkynes having fluoroalkyl and aryl groups took place smoothly with good regioselectivity (ca. 80:20). In sharp contrast, the reaction of the alkynes having a fluoroalkyl group and a benzyl-type substituent, or various propargyl alcohols gave the corresponding vinylsilanes in an excellent regio- and stereoselective manner. Treatment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…This is contrary to the steric environment around the alkyne and is clearly showing preference for hydride attack at the more electrophilic terminus of the alkyne. 23,47,63,64 Indeed, Alami observed this effect when applied to the palladium catalyzed hydrostannylation of 13, with 4 : 1 regioselectivity for β-substitution being observed. 65 They also showed that the regioselectivity in these systems directly correlated to the Hammett σ-value for substituted benzene rings.…”
Section: Internal Alkynesmentioning
confidence: 94%
“…This is contrary to the steric environment around the alkyne and is clearly showing preference for hydride attack at the more electrophilic terminus of the alkyne. 23,47,63,64 Indeed, Alami observed this effect when applied to the palladium catalyzed hydrostannylation of 13, with 4 : 1 regioselectivity for β-substitution being observed. 65 They also showed that the regioselectivity in these systems directly correlated to the Hammett σ-value for substituted benzene rings.…”
Section: Internal Alkynesmentioning
confidence: 94%
“…Since a CF 3 group has a very strong electron-withdrawing ability, the CF 3 C α —Cu III bond may be stronger than Cu III —C β . (In the hydrometalation and the carbometalation reaction of fluoroalkylated alkynes, the same regioselectivity was observed [3235]. ) Accordingly, a transfer of the R 2 group on Cu III to the olefinic carbon distal to a CF 3 group may take place preferably, with vinylcopper intermediate Int-E , not Int-F , being produced exclusively.…”
Section: Resultsmentioning
confidence: 75%
“…2). 18 Hydro-and carbocupration of 9 were also developed by the same group and excellent regio-and stereoselectivities were noticed. 19 However, only potent electrophiles could be used to trap the intermediate vinylcopper species 13 (Scheme 3, eq.…”
mentioning
confidence: 93%